The Stratification of Abu al-Shiddiq (w.108 H) and Qatadah (w. 118 H) in the Narration of the al-Mahdi Hadith - Syamsudin, Kinkin; Rodliyana, M. Dede (Universitas Islam Negeri K.H. Abdurrahman Wahid Pekalongan, 2022)
This article examines the influence of differences of rawi stratification on hadith narration, using Ibn Khaldun's stratification theory as outlined in his book entitled Muqaddimah. This study employs library research with a content analysis approach, focusing on hadiths about al-Mahdi narrated through the paths of Abu al-Shiddiq (d. 108 H) and Abu Nadhrah (d. 103 H). The findings reveal that Qatadah, the principal student of Abu al-Shiddiq, did not receive the narration about al-Mahdi from his teacher but rather from Abu Nadhrah. Although the three rawis differ in the number of narrations—Qatadah (12,209 narrations), Abu al-Shiddiq (183 narrations), and Abu Nadhrah (1,181 narrations)—all are considered thiqah (trustworthy narrators). The study concludes that differences of stratification among the three narrators are not the reason why Qatadah did not narrate the al-Mahdi hadith from Abu al-Shiddiq. This research contributes to academic discourse by offering a new perspective on the application of Ibn Khaldun's stratification theory in the study of hadith narration. It also highlights that the number of narrations and stratification positions do not always determine specific narration paths. Future research is recommended to expand the scope of analysis to other rawis using a similar approach to gain deeper insights into the relationship between rawi stratification and hadith narration.